A Benchmark Side-by-Side Comparison of Two Well-Established Protocols for in vitro Hematopoietic Differentiation From Human Pluripotent Stem Cells - Gutierrez-Agüera, Francisco; Rodriguez-Cortez, Virginia; Petazzi, Paolo; Bueno, Clara; Menendez, Pablo (Frontiers in Cell and Developmental Biology, 2021)
The generation of transplantable hematopoietic stem cells (HSCs) from human pluripotent stem cells (hPSCs) remains challenging. Current differentiation protocols from hPSCs generate mostly hematopoietic progenitors of the primitive HSC-independent program, and it remains unclear what is the best combination of cytokines and hematopoietic growth factors (HGFs) for obtaining functional hematopoietic cells in vitro. Here, we have used the AND1 and H9 hESC lines and the H9:dual-reporter RUNX1C-GFP-SOX17-Cherry to compare the hematopoietic differentiation in vitro based on the treatment of embryoid bodies (EBs) with the ventral mesoderm inducer BMP4 plus HGFs in the absence (protocol 1) or presence (protocol 2) of stage-specific activation of Wnt/β-catenin and inhibition of Activin/Nodal. Despite a slight trend in favor of protocol 1, no statistically significant differences were observed between protocols at any time point analyzed throughout EB development regarding the frequency of hemogenic endothelial (HE) precursors; CD43+ CD45−, CD45+, and CD45 + CD34 + hematopoietic derivatives; or the output of clonogenic progenitors. Similarly, the kinetics of emergence throughout EB development of both SOX17 + HE and RUNX1C + definitive hematopoiesis was very similar for both protocols. The expression of the early master mesendodermal transcription factors Brachyury, MIXL1, and KDR revealed similar gene expression kinetics prior to the emergence of RUNX1C + definitive hematopoiesis for both protocols. Collectively, the simpler protocol 1 is, at least, as efficient as protocol 2, suggesting that supplementation with additional morphogens/HGFs and modulation of Activin/Nodal and Wnt/β-catenin pathways seem dispensable for in vitro hematopoietic differentiation of hPSCs.